Differential Effects of Parkinson’s Disease on Interneuron Subtypes within the Human Anterior Olfactory Nucleus - Ubeda-Bañon, Isabel; Flores-Cuadrado, Alicia; Saiz-Sanchez, Daniel; Martinez-Marcos, Alino (Frontiers in Neuroanatomy, 2017)
Synucleinopathies (including α-synucleinopathies), which include Parkinson’s disease, manifest themsevles early on (stage 1) in the olfactory system; preferentially in the anterior olfactory nucleus. In particular, the non-motor, early manifestations of Parkinson’s disease include hyposmia, which is the partial loss of the sense of smell. The neural basis of hyposmia in Parkinson’s disease, however, is poorly understood; but the anterior olfactory nucleus appears to be a key structure in the disease’s progression. We analyzed whether α-synuclein was involved in the differential interneuron vulnerability associated with Parkinson’s disease in the retrobulbar, cortical anterior and cortical posterior divisions of the anterior olfactory nucleus. First, we determined the expression of the calcium binding interneuron markers, calretinin, calbindin, and parvalbumin, as well as non-calcium binding interneuron marker, somatostatin, in neuronal cell bodies alone (cells/mm2) and in neuronal cell bodies and neurites (% of area fraction) of post-mortem tissue from Parkinson’s disease cases and age-matched controls (n = 4 for each) by immunofluorescent confocal microscopy. Results indicated that parvalbumin expression was upregulated in neuronal cell bodies throughout the anteior olfactory nucleus of Parkinson’s disease cases compared with controls. Furthermore, there was increased calbindin, calretinin, and parvalbumin expression in the cell bodies and neurites of neurons in the retrobulbar division and also increased parvalbumin expression in the neurites of neurons in the cortical division; calretinin expression was also increased in neuronal cell bodies and neurites in the cortical posterior division. Second, we analyzed the co-localization of the above markers with α-synuclein, with results indicating that α-synuclein co-localized with the calcium-binding proteins, but only partially with somatostatin. Taken together, these results indicate differential expression levels among different neural markers in the divisions of the anterior olfactory nucleus in Parkinson’s disease cases and point to several possibilities, among them: possible neuroprotective mechanisms of calcium-binding proteins against α-synuclein; and the differential involvement of somatostatin in α-synuclein-positive cell bodies and neurites.